The world's greatest elephant - Helfer, Ralph (Philomel Books, 2006)
Born on the same day in the same German town, Bram and his elephant, Modoc, grew up side by side. Their circus act brought them wide fame, but their incredible bond would also lead to a series of adventures with danger at every turn.